The policing mind : developing trauma resilience for a new era - Miller, Jessica K. (Bristol, UK : Policy Press, 2022)
How does it feel to be a police officer? Jessica Miller uses the most recent neuroscience and real-life examples to explore risks to individual resilience. A compulsory read for anyone with an interest in policing, the book offers practical resilience techniques and policy recommendations for police officers facing crime in a post-COVID world.
Feeling disproportionately anxious about a harmless interaction? (fear in interpersonal interaction):14 how to imagine life from someone else's disadvantage -- From F-word to C-bomb -- When the day's events are a heavy weight to carry home -- create clear boundaries between job and not-job -- Boots-at-the-door -- Constructing a personal story in your mind about an incident?: acknowledging the discomfort and neutralising the narrative in your head -- Labelling 'there is...' -- Getting creative (bit weird) -- Tips
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 11, 2022).
JSTOR
Keywords: Police psychology; Resilience (Personality trait); Psychologie policière.; Résilience (Trait de personnalité); SOCIAL SCIENCE / Criminology; Resilience (Personality trait); Police psychology